Strategies for Promoting Social Justice in Rural Educational Access - Wanjala, Otieno; Mwangi, Kamau; Chege, Baraka (Journal Social Humanity Perspective, 2025)
This study aims to explore how social justice is perceived, experienced, and promoted in educational access within rural communities in Kenya. Recognizing persistent disparities in infrastructure, resources, and inclusion, the research investigates the barriers learners face, the strategies employed by communities and institutions, and how these dynamics influence equitable educational opportunities. The study employed a qualitative research design. Participants included 30 individuals comprising students, parents, teachers, and local education officials, selected purposively to ensure rich insights into the phenomenon. Data were collected through semi-structured interviews, observations in schools and community settings, and document analysis of relevant policies and school reports. Thematic analysis was employed to identify patterns and generate themes related to social justice perceptions, barriers to access, and strategies to enhance equity. Findings reveal that social justice in education is understood by participants as fairness, inclusion, and equitable resource distribution. Significant barriers include inadequate infrastructure, socio-economic constraints, teacher shortages, and gendered cultural expectations. Community-led initiatives, government interventions, and NGO support emerged as key strategies for promoting access, though their effectiveness depends on management, coordination, and sustainability. Learners’ interpretations of visual and physical elements in schools further highlight the importance of perceived equity in shaping engagement and motivation. Advancing social justice in rural education requires integrated management approaches, equity-oriented leadership, targeted resource allocation, and collaborative stakeholder engagement. The study underscores that social justice is not only a normative ideal but a practical, operational imperative that demands context-sensitive strategies to transform policy frameworks into meaningful and inclusive educational opportunities.